Pengolahan Pakan Ikan Berbahan Dasar Alternatif di Komunitas Budidaya Ikan Dalam Ember - Maya Istyadji; Yudha Irhasyuarna; Yasmine Khairunnisa (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
This community service activity aims to provide knowledge and training for students and the community in Sungai Besar, Banjarbaru, regarding fish farming in buckets, especially in terms of making fish feed by using alternative base materials for the survival of fish in buckets. Participant responses were obtained from a response questionnaire distributed to participants consisting of eight statements in the form of a Likert scale 1 – 4. From the implementation results, it was found that 95.83% of participants stated that the material presented during the training added to participants' insights about making alternative-based fish feeds. In addition, participants stated that the training was quite interactive. However, in terms of the use of tools and materials, administrative processes, and the media in the delivery of socialization materials still need to be improved so that this training activity gets more optimal results.